Antitumor imidazo[5, 1-d]-1, 2, 3, 5-tetrazines: compounds modified at the 3-position overcome resistance in human glioblastoma cell lines12. Issue 12 (3rd October 2016) - Cousin, David; Zhang, Jihong; Hummersone, Marc G.; Matthews, Charles S.; Frigerio, Mark; Bradshaw, Tracey D.; Stevens, Malcolm F. G.
Abstract : Imidazotetrazines substituted at the N-3 position overcome resistance or tolerance to temozolomide conferred, respectively, by MGMT or DNA MMR defects. Abstract : Synthetic routes to 3-substituted imidazo[5, 1- d ]-1, 2, 3, 5-tetrazines structurally related to temozolomide were explored. Interaction of 4-diazoimidazole-5-carboxamide with an isocyanate afforded high product yields when the isocyanate was available in acceptable purity. Alternatively, alkylation of the nor-temozolomide anion afforded high yields of new imidazotetrazines. Several compounds, evaluated against a panel containing matched MGMT± glioma cell lines, showed equal inhibitory activity irrespective of MGMT status; the N3-propargyl-imidazotetrazine (10m ) was prioritised as an alternative to temozolomide able to bypass drug-resistance mechanisms. In Taq polymerase assays10m, like temozolomide and its ring-opened counterpart MTIC, alkylated DNA at clusters of three and five guanine residues; covalent modification of N-7 sites of guanine were detected in piperidine cleavage assays. Compound10m did not cross-link DNA but induced double-strand breaks evidenced by γ-H2AX detection. Propargyl-substituted imidazotriazene (13g ), showed comparable activity to10m indicating that ring-opening of the bicyclic nucleus of novel imidazotetrazine is probably required for activity.